Observasi Supervisi Kependidikan Terhadap Peningkatan Hasil Kompetensi Dan Kinerja Guru Dalam Kegiatan Belajar Mengajar Di SMP Negeri 3 Muntok Kabupaten Bangka Barat Tahun Pelajaran 2022/2023 - Ida Safrina (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Apart from functioning as a managerial supervisor, the principal also functions as an academic supervisor. As an academic supervisor, the principal has an obligation to help teachers become professionals so that teachers can improve the quality of the learning process. Apart from also acting as an educational consultant who always becomes a companion for teachers in improving the quality of education. This School Action Research (PTS) aims to improve teacher competency and performance results in teaching and learning activities through educational supervision observations at SMP Negeri 3 Muntok, West Bangka Regency, The subjects of School Action Research are teachers who teach at SMP Negeri 3 Muntok, Muntok District, West Bangka Regency, Academic Year 2022/2022. The results showed that supervision at SMP Negeri 3 Muntok increased by 21.67% in cycle I and 14.66% in cycle II. In detail, for teacher 1, the initial condition was an average of 53.33, the first cycle averaged 75.00, an increase of 20.00%, the second cycle averaged 91.25, an increase of 16.25%. Teacher 2 initial condition averaged 55.00, first cycle averaged 80.00, increased 25.00%, second cycle averaged 91.25, increased 10.25%. Teacher 3 initial conditions average 50, cycle I average 70, an increase of 20.00%, cycle II average 87.50, increase 17.25%. The results achieved by the teacher have met the target, namely by comparing the results with a minimum increase of 10%. Based on the research results above, it can be concluded that through Supervision Observation, Teacher Competency and Performance Results in Teaching and Learning Activities at SMP Negeri 3 Muntok can be improved.